Glycine receptor antibodies in a boy with focal epilepsy and episodic behavioral disorder - Wuerfel, E; Bien, C; Vincent, A; Woodhall, M; Brockmann, K (Elsevier, 2014)
A wide range of clinical presentations including neuromuscular disorders and autoimmune encephalopathies is being recognized to be associated with various autoantibodies. Glycine receptor (GlyR) antibodies have so far been found mainly in adult patients with phenotypes comprising progressive encephalomyelitis with rigidity and myoclonus or stiff-person syndrome. We report a four-year-old boy who presented with a two-year-history of drug-resistant focal epilepsy with unusual seizure semiology, temper tantrums, headache, clumsiness, and intermittently impaired speech. While MRI and CSF were normal, screening for autoimmune antibodies revealed GlyR antibodies in serum. Immunomodulatory treatment with steroids resulted in rapid and complete resolution of symptoms. Our observation widens the spectrum of clinical presentations associated with GlyR antibodies and emphasizes the potential relevance of neuronal autoantibodies in epilepsies of unknown cause in children as well as in adults. © 2014 Elsevier B.V.